2018
DOI: 10.1016/j.jmig.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescription and Patient Use After Gynecologic Procedures: A Survey of Patients and Providers

Abstract: With respect to the physician survey, we conclude there is a wide range of opioid prescription practices and patient opioid consumption after gynecologic surgery. The patient survey revealed that physicians prescribe fewer opioid tablets after a minimally invasive approach to hysterectomy versus open hysterectomy. However, most patients use less than half of prescribed opioids, and a fraction did not use any opioids at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…One study in Boston compared the prescribing patterns and usage of opioids following minimally invasive and abdominal hysterectomies. They found that 64.6% of patients used less than half of prescribed opioids, and that 16.1% of patients did not use any of their prescribed pills . A separate study from Massachusetts asked patients to complete a questionnaire “regarding the number of tablets prescribed and used” 2 weeks following urogynecologic and reconstructive surgeries .…”
Section: Introductionmentioning
confidence: 99%
“…One study in Boston compared the prescribing patterns and usage of opioids following minimally invasive and abdominal hysterectomies. They found that 64.6% of patients used less than half of prescribed opioids, and that 16.1% of patients did not use any of their prescribed pills . A separate study from Massachusetts asked patients to complete a questionnaire “regarding the number of tablets prescribed and used” 2 weeks following urogynecologic and reconstructive surgeries .…”
Section: Introductionmentioning
confidence: 99%
“…Our survey response rate was nearly 60%, with potential that the data from the missing 40% of the patient cohort may have altered the associations identified among total opioid use among physician ERAS-adherence groups. The duration of the study period was determined based on the goal of recruiting and surveying over 100 study participants, consistent with the sample size of prior similar investigations [4,5]. However, we were only able to include a small number of vaginal hysterectomies as well as vaginal and vulvar surgeries and would have benefited from a longer study period to better comment on the role of opioid use in these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid overprescribing after benign gynecology surgery could result from heterogeneous physician-prescribing patterns [5]. The absence of a national consensus guideline regarding postoperative analgesic management and varying professional opinions regarding opioid prescribing has led many institutions to implement their own postoperative opioid prescribing recommendations as a component of their Enhanced Recovery After Surgery (ERAS) protocols.…”
mentioning
confidence: 99%
“…We chose to investigate the effects of a new standard low-tablet number opioid prescription in the ambulatory surgery setting. Although robotic surgeries and laparoscopic hysterectomies may have similar analgesic requirements [1,3,11,12] and may be done in an outpatient setting, we wanted to focus on common ambulatory surgeries. There are not sufficient data available to guide prescribing practices in this population.…”
Section: Tablementioning
confidence: 99%